Pelatihan Pengendalian Faktor Risiko Hipertensi Pada Kader Kesehatan Posbindu Di Wilayah Kerja Puskesmas Sungai Ulin Kota Banjarbaru - Roswita, Ria; Jannah, Raudatul; Ristiana, Ana (UPPM Poltekkes Kemenkes Banjarmasin, 2024)
The prevalence rate of hypertension in South Kalimantan is at the top in Indonesia at 44.13% (Riskesdas, 2018). One of the causes of the increase in the number of hypertension cases in 2021 in Banjarbaru City is because the implementation of controlling NCD (Hypertension) risk factors still relies on health workers at health centers. The aim of this community service is to increase the knowledge and skills of cadres related to controlling NCD (Hypertension) risk factors as well as target partner services regarding measuring Hypertension risk factors, examining Hypertension risk factors and educating on the prevention and control of Hypertension risk factors through Posbindu non communicable disease (NCD). The implementation of this community service activity consists of two activities, health volunteers training and monitoring the implementation of hypertension risk factor control by health volunteers at Posbindu. The results of this community service were an increase in the average knowledge and skills of cadres in controlling hypertension risk factors.